Hydrogen deuterium exchange and other mass spectrometry- based approaches for epitope mapping - Jethva, Prashant N.; Gross, Michael L. (Frontiers in Analytical Science, 2023)
Antigen-antibody interactions are a fundamental subset of protein-protein interactions responsible for the “survival of the fittest”. Determining the interacting interface of the antigen, called an epitope, and that on the antibody, called a paratope, is crucial to antibody development. Because each antigen presents multiple epitopes (unique footprints), sophisticated approaches are required to determine the target region for a given antibody. Although X-ray crystallography, Cryo-EM, and nuclear magnetic resonance can provide atomic details of an epitope, they are often laborious, poor in throughput, and insensitive. Mass spectrometry-based approaches offer rapid turnaround, intermediate structural resolution, and virtually no size limit for the antigen, making them a vital approach for epitope mapping. In this review, we describe in detail the principles of hydrogen deuterium exchange mass spectrometry in application to epitope mapping. We also show that a combination of MS-based approaches can assist or complement epitope mapping and push the limit of structural resolution to the residue level. We describe in detail the MS methods used in epitope mapping, provide our perspective about the approaches, and focus on elucidating the role that HDX-MS is playing now and in the future by organizing a discussion centered around several prototype instrument/applications improvement used for epitope mapping. At the end, we provide a tabular summary of the current literature on HDX-MS-based epitope mapping.